Pengaruh Bahan Bakar Campuran Biodiesel Berbahan Dasar Minyak Sawit terhadap Elastomer NBR - Wimada, Andrias Rahman; Sholihah, Maharani Dewi; Karuana, Feri; Arisanti, Anisa Galuh; Ghazidin, Hafisd; Chalid, Mochamad (Rekayasa Material, Manufaktur dan Energi, 2023)
The government implemented the use of a 30% biodiesel mixture in diesel fuel for all types of sectors in 2020. In the upcoming years, this policy will probably continue to be strengthened. The compatibility of the elastomers (seals, gaskets, and O-rings) used in the fuel system needs to be carefully considered, though, as biodiesel may have an adverse effect on components composed of natural rubber or synthetic rubber. This study aims to determine the compatibility of elastomeric fuel mixtures of 30% and 40% biodiesel based palm oil (CPO) in Indonesia. The elastomer used in this study, acrylonitrile butadiene rubber (NBR), is frequently utilized in the automobile industry or in fuel storage systems in the production of electricity, mining, and other industries. Using the ASTM D471 technique, the compatibility of this elastomer is evaluated based on mass swelling, swelling volume, tensile strength, and hardness. It was discovered by mass swelling, swelling volume, tensile strength, and hardness tests that the compatibility of acrylonitrile butadiene rubber diminishes with increasing biodiesel content (FAME).